Table S5 from Genomic and Transcriptomic Characteristics of Metastatic Thyroid Cancers with Exceptional Responses to Radioactive Iodine Therapy - Laura Boucai (15054310) (2025)
Expression of chr1q genes in BRAFV600E with chr1q gain and copy number quiet tumors in the TCGA RNAseq dataset.